Dynamic programming approach for road centerline extraction from digital images - Do Vale, Giovane Maia [UNESP]; Dal Poz, Aluir Porfirio [UNESP] (My University, 2004)
This paper presents a dynamic programming approach for semi-automated road extraction from medium-and high-resolution images. This method is a modified version of a pre-existing dynamic programming method for road extraction from low-resolution images. The basic assumption of this pre-existing method is that roads manifest as lines in low-resolution images (pixel footprint> 2 m) and as such can be modeled and extracted as linear features. On the other hand, roads manifest as ribbon features in medium- and high-resolution images (pixel footprint ≤ 2 m) and, as a result, the focus of road extraction becomes the road centerlines. The original method can not accurately extract road centerlines from medium- and high- resolution images. In view of this, we propose a modification of the merit function of the original approach, which is carried out by a constraint function embedding road edge properties. Experimental results demonstrated the modified algorithm's potential in extracting road centerlines from medium- and high-resolution images.
Keywords: Algorithms; Edge detection; Functions; Image processing; Optical resolving power; High-resolution images; Ribbon features; Road edge properties; Semi-automated road extraction; Dynamic programming; digital image; image analysis; pixel; road